Mental stress among patients undergoing orthodontic treatment during coronavirus-19 global pandemic - Sherchan, Prabesh; Gurung, Deepa; Bogati, Subekshya; Gupta, Sujaya (Journal of Kathmandu Medical College, 2022)
Background: Coronavirus disease 2019 (COVID-19) is the most recent disease of corona virus family that impacted people all over the world. Subsequent lockdown and fear of disease transmission greatly affected the orthodontic appointments, treatments, as well as mental health.Objectives: To assess the mental stress among patients undergoing orthodontic patients during COVID-19 pandemic.Methods: A descriptive cross-sectional study was conducted among individuals undergoing orthodontic treatment in the department of Orthodontics and Dentofacial Orthopaedics in Dental Hospital of Kathmandu Medical College from 2020 December to 2021 February after institutional ethical approval. Data were collected from 108 participants by convenience sampling technique using questionnaire. Exclusion criteria included patients who answered